Characteristics of non-fatal overdoses and associated risk factors in patients attending a specialist community-based substance misuse service. Issue 4 (August 2022) - Ghose, Riya; Cowden, Fiona; Veluchamy, Abirami; Smith, Blair H; Colvin, Lesley A
Introduction: There are concerns about rising drug-related deaths and the potential contribution of prescription analgesics. There is limited understanding regarding the role of prescription analgesics in non-fatal overdoses (NFODs), nor is there a good understanding of what factors are associated with more severe overdose. Objectives: To explore risk factors and characteristics of NFODs among people attending a specialist community-based substance misuse service. Methods: After Caldicott approval, data on NFODs, in people attending the Tayside Substance Misuse Service (TSMS), were extracted from the Scottish Ambulance Service database, along with opioid replacement therapy (ORT) prescribing data. Statistical analysis was performed using R studio and Microsoft Excel. Results: 557 people (78% [434/556] male, mean age ± standard deviation 38.4 ± 7.95) had an NFOD. Repeat NFODs were more likely in males compared to females ( p < .0065). Males were more likely to be administered naloxone (OR = 1.94, 95% CI = 1.10–3.40, p < .02). NFODs at home were more likely to be moderate to severe (categorized by Glasgow Comma Scale [ p < .02, OR = 4.95, 95% CI = 1.24–24.38]). Methadone (321/557, 57.63%), benzodiazepines (281/557, 50.45%) and heroin (244/557, 43.81%) were the commonest substances: prescribed methadone overdose was more likely than buprenorphine ( p < .00001). Opioids and benzodiazepines were often taken together (275/557, 49.40%), with almost all gabapentinoid NFODs also involving opioids (60/61, 98.40%). Conclusions: Polysubstance use with opioids prescribed for ORT, such as methadone, is highly likely to be implicated in NFOD, with males being at the highest risk of severe and repeat NFOD. Future work should focus on strategies to further reduce NFODs.